Analysis of Conversational Implicature in the Hobbit Movies Subtitle - Na?mah, Inayatun; Sugirin, Sugirin (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
This study aimed to analyze the translations of conversational implicatures in The Hobbit movies subtitle. In addition this study tried to describe the pragmatic shifts between the source text (movies script) and the target text (movie subtitle). Furthermore, this study tried to identify the translations techniques applied by the subtitler in translating conversational implicatures in The Hobbit movies. This was a descriptive qualitative study. The data of this study was the subtitle of The Hobbit movies in forms of words, phrase, clause, and sentence which contained implicature. The results showed that there were 10 translation techniques applied by the subtitler to transfer the implicit meanings of conversational implicatures in The Hobbit Movies. Those were literal, reduction, modulation, linguistic amplification, borrowing, transposition, adaptation, compensation, substitution, and linguistic compression. Those techniques were applied in various frequencies. Moreover, the result of pragmatic shifts showed that there were 95 conversational implicatures found in The Hobbit movies. Most of those were well translated. This could be seen from the percentage of pragmatic shifts that was 25 % data of implicatures showed pragmatic shifts.